All-solid-state batteries designed for operation under extreme cold conditions - Bolong Hong; Lei Gao; Changping Li; Genming Lai; Jinlong Zhu; Dubin Huang; Yunxing Zuo; Wen Yin; Mengyu Sun; Shusen Zhao; Jiaxin Zheng; Songbai Han; et al. (Nature Communications)
Abstract A pressing need for enhancing lithium-ion battery (LIB) performance exists, particularly in ensuring reliable operation under extreme cold conditions. All-solid-state batteries (ASSBs) offer a promising solution to the challenges posed by conventional LIBs with liquid electrolytes in low-temperature environments. In this study, leveraging the benefits of amorphous solid-state electrolytes (SSEs) xLi3N-TaCl5 (1 ≤ 3x ≤ 2), we develop ASSBs capable of functioning effectively under extreme cold conditions. The designed ASSBs, employing LiCoO2 positive electrode with a mass loading of 4.46 mg cm‒2 and a Li-In negative electrode, demonstrate initial discharge capacities of 183.19, 164.8 and 143.78 mAh g‒1 under 18 mA g‒1 at ‒10, ‒30, and ‒40 °C, respectively, and exhibit a final discharge capacity of 137.6 mAh g‒1 at 18 mA g‒1 and ‒30 °C in the 100th cycle. Moreover, the ASSBs demonstrate an initial discharge capacity of 51.94 mAh g‒1 at 18 mA g‒1 and ‒60 °C with cycling over 200 h.